Gastric banding-associated weight loss diminishes hepatic Tsukushi expression. (September 2020) - Grander, Christoph; Jaschke, Nikolai; Enrich, Barbara; Grabherr, Felix; Mayr, Lisa; Schwärzler, Julian; Effenberger, Maria; Adolph, Timon E.; Tilg, Herbert
Graphical abstract: Highlights: Hepatic TSK expression is reduced six months after LAGB which is mainly driven by weight loss. Hepatic TSK expression directly correlates with weight loss and indirectly correlates with histological severity of liver disease. TSK might reflect a promising target for treating obesity and NAFLD. Abstract: Obesity has emerged as a substantial global healthcare issue that is frequently associated with insulin resistance and non-alcoholic fatty liver disease (NAFLD). Tsukushi (TSK), a liver-derived molecule, was recently identified as a major driver of NAFLD. Laparoscopic adjustable gastric banding (LAGB) has proven effective in reducing body weight and improving NAFLD. We therefore aimed to investigate the relation between LAGB-induced weight loss and TSK expression. Twenty-six obese patients undergoing LAGB were included in the study and metabolic parameters were assessed before (t0) and six months after LAGB (t6). The expression of TSK in liver and subcutaneous adipose tissue (AT) specimens was determined at both time points. To unravel regulatory mechanisms of TSK expression, human peripheral blood mononuclear cells (PBMCs) were stimulated with pro-inflammatory cytokines and TSK mRNA levels were analyzed by quantitative polymerase chain reaction. LAGB induced pronounced weight loss which was paralleled by amelioration of metabolic disturbances and histologically defined NAFLD. While hepatic TSK expression was markedly decreased after LAGB, adipose tissue TSK expression remained comparable to baseline. The decline in hepatic TSK expression after LAGB positively correlated with weight loss and the reduction in BMI, and negatively correlated with NAFLD activity score (NAS). In human PBMCs, pro-inflammatory cytokines such as IL-1β and TNFα induced the expression of TSK . In conclusion, LAGB-induced weight loss reduces hepatic TSK expression. Inhibiting TSK might represent a promising target for treating NAFLD in the future.